2011
DOI: 10.1002/chem.201003423
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic Michael–Alkylation Cascade: The Enantioselective Nitrocyclopropanation of Oxindoles

Abstract: The spiro saga goes on! The title reaction sequence provides the first enantioselective synthesis of spiro nitrocyclopropyl oxindoles. The method provides easy access to these new, biologically inspired compounds from readily available starting materials (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(54 citation statements)
references
References 81 publications
1
53
0
Order By: Relevance
“…More recently, Bartoli et al have reported the enantioselective nitrocyclopropanation of oxindoles 168a-d with bromonitromethane which was induced through hydrogen-bonding activation mode by 9-epi-9-thiourea-9-deoxydihydroquinidine 169 in the presence of NaHCO 3 . [86] As shown in Scheme 46, the corresponding spiro nitrocyclopropyl oxindoles 170a-d were achieved in good to high yields, moderate to high diastereoselectivities, and excellent enantioselectivities of up to 98% ee.…”
Section: Domino Michael-intramolecular Alkylation Reactionsmentioning
confidence: 97%
“…More recently, Bartoli et al have reported the enantioselective nitrocyclopropanation of oxindoles 168a-d with bromonitromethane which was induced through hydrogen-bonding activation mode by 9-epi-9-thiourea-9-deoxydihydroquinidine 169 in the presence of NaHCO 3 . [86] As shown in Scheme 46, the corresponding spiro nitrocyclopropyl oxindoles 170a-d were achieved in good to high yields, moderate to high diastereoselectivities, and excellent enantioselectivities of up to 98% ee.…”
Section: Domino Michael-intramolecular Alkylation Reactionsmentioning
confidence: 97%
“…In 2011, Bartoli and Bencivenni developed a highly efficient asymmetric approach to spiro cyclopropyl oxindoles 7 with three adjacent stereogenic centers based on an organocatalytic Michael–alkylation cascade sequence of methyleneindolinones and halonitroalkanes 5 (Scheme ) 37. The reaction was efficiently catalyzed by the bifunctional catalyst 6 , rendering the final spiro cyclopropyl oxindoles 7 in good yields, diastereoselectivities and enantioselectivities.…”
Section: Three‐membered Fused Ringsmentioning
confidence: 99%
“…70 The efficiency of the reaction proved to be highly solvent dependent with the optimum reaction conditions found with methyl t-butyl ether (MTBE) and one equivalent of Na 2 CO 3 . In 2011, Bencivenni and co-workers disclosed the first enantioselective nitrocyclopropanation of 3-alkylidene oxindoles and bromonitroalkyl derivatives with thiourea catalyst 15 (Scheme 23).…”
Section: Scheme 14mentioning
confidence: 99%